Restricted Visual Scanpaths During Emotion Recognition in Childhood Social Anxiety Disorder - Kleberg, Johan Lundin; Löwenberg, Emilie Bäcklin; Lau, Jennifer Y. F.; Serlachius, Eva; Högström, Jens (Frontiers in Psychiatry, 2021)
Background. Social anxiety disorder (SAD) has its typical onset in childhood and adolescence. Maladaptive processing of social information may contribute to the etiology and maintenance. During face perception, individuals extract information with a succession of visual fixations known as a scanpath. Atypically long scanpaths have been reported in adults with SAD, but no data exists from pediatric samples. SAD has also been linked to atypical arousal. Both metrics were examined in one of the largest eye-tracking studies of pediatric SAD to date Methods. Children and adolescents with SAD (n = 62) and healthy controls (n = 39) completed an emotion recognition task. The visual scanpath and pupil dilation (an indirect index of arousal) were examined. The analysis plan was preregistered. Results. Youth with SAD showed restricted scanpaths, a finding supported by both frequentist and Bayesian statistics. Higher pupil dilation was also observed in the SAD group, but despite a statistically significant group difference, this result was not supported by the Bayesian analysis. Conclusions. Findings are contrary to findings from adult studies, but similar to what has been reported in neurodevelopmental conditions associated with social interaction impairments. Restricted scanpaths may disrupt holistic representation of faces known to favor adaptive social understanding.